Breakthrough COVID‐19 after SARS‐CoV‐2 vaccination in solid organ transplant recipients: An analysis of symptomatic cases and monoclonal antibody therapy. Issue 2 (31st January 2022) - Yetmar, Zachary A.; Bhaimia, Eric; Bierle, Dennis M.; Ganesh, Ravindra; Razonable, Raymund R.
Abstract: Background: Solid organ transplant (SOT) recipients are at increased risk for complications from SARS‐CoV‐2 infection. Little is known regarding clinical course and outcomes of breakthrough COVID‐19 in the fully vaccinated SOT population. We sought to describe our cohort of SOT recipients who developed symptomatic breakthrough COVID‐19 after full vaccination. Methods: We conducted a retrospective review of SOT recipients diagnosed with COVID‐19 at least 14 days after completing SARS‐CoV‐2 vaccination. Patients were analyzed according to those presenting with mild‐to‐moderate and severe COVID‐19, respectively. We described presenting characteristics, COVID‐19 therapy, and analyzed outcomes including emergency department (ED) visits, hospitalization, and intensive care unit (ICU) admission. Results: Thirty‐five patients met inclusion criteria. These had a mean age of 60.8 years and kidney transplant was the most common SOT type. Five patients presented with severe COVID‐19 at diagnosis, all requiring hospitalization without ICU admission. From the 30 patients who presented with mild‐to‐moderate infection, 28 received casirivimab–imdevimab. Four of these 28 (14.3%) had an ED visit, with one requiring hospital admission (3.4%). No patients required ICU admission. Conclusion: Breakthrough COVID‐19 may occur in SOT recipients after full vaccination, though they appear to have acceptable outcomes. Anti‐spike monoclonal antibody therapy for eligible SOT patients may have mitigated clinical progression and improved the outcomes. Further study with large cohorts is warranted.